Effect of Occupation and Household Income on the Financial Knowledge of Working Class of National Capital Region of India - Ms. Poonam Rani; Dr. Khujan Singh (International Journal of Management Studies (IJMS), 2021)
The objective of this study is to check the effect of occupation and household income on the financial knowledge of working class of national capital region of India. To achieve this objective, the data has been collected from 596 respondents through an adapted questionnaire. The data has been analyzed by using one-way ANOVA. The level of financial knowledge among Bankers and Lawyers have been found on an average more than three on the basis of five point Likert scale in comparison to the teachers, doctors and other professionals. Respondents of different professions have different level of financial knowledge with regards to the various interest rates and financial plan. The finding of the study revealed that the profession of the respondents effects their level of financial knowledge. Whereas, the level of income of working class do not affect their level of financial knowledge.